COBALAMIN DEFICIENCY IN THE ELDERLY - Giacomo Marchi; Fabiana Busti; Acaynne Lira Zidanes; Alice Vianello; Domenico Girelli (Mediterranean Journal of Hematology and Infectious Diseases, 2020)
Older people are at risk for cobalamin (vitamin B12) deficiency because of a number of common disorders (e.g. autoimmune gastritis) and drugs (e.g. antacids) that may alter its absorption and utilization. The prevalence of cobalamin deficiency increases with age, resulting particularly elevated in frail and institutionalized subjects. At variance with common sense, the diagnosis is far from simple and requires a high degree of suspicion, due to heterogeneity and non-specificity of the signs and symptoms, ranging from macrocytosis (with or without anemia) to neuropsychiatric manifestations, that characterize several other aging-related disorders, like hematological malignancies, diabetes, hypothyroidism or vasculopathies. Furthermore, the detection of low levels of serum vitamin B12 appears poorly sensitive and specific. Other biomarkers, like serum homocysteine or methylmalonic acid, have improved the diagnostic possibilities but are expensive, not widely available and may be influenced by some confounders (e.g. folate deficiency, or chronic renal failure). Early recognition and treatment are crucial, since a proportion of patients develop severe complications, such as bone marrow failure and irreversible neurological impairment. High-dose oral treatment has proven to be as effective as the parenteral route even in subjects with malabsorption, ensuring the complete resolution in the majority of cases. In this review, we trace the essential role of cobalamin in humans, the possible causes and impact of deficiency, the diagnostic challenges and the therapeutic options, between old and emerging concepts, with a particular focus on the elderly.